Increased Serum Level of IGF‐1 Correlates With Better Cognitive Status in End‐Stage Renal Disease Patients Undergoing Hemodialysis. Issue 2 (7th December 2017) - Prelevic, Vladimir; Radunovic, Danilo; Antunovic, Tanja; Ratkovic, Marina; Gligorovic‐Bahranovic, Najdana; Gledovic, Branka; Vujosevic, Snezana; Nedovic‐Vukovic, Mirjana; Basic‐Jukic, Nikolina
Abstract: Prevalence of cognitive function decline in end stage renal disease (ESRD) patients undergoing hemodialysis is higher than in the general population. We analyzed risk factors for cognitive function decline in those patients. This study included 93 ESRD patients undergoing hemodialysis two or three times a week in three centers for hemodialysis in Montenegro. The cognitive status of patients was assessed using the mini mental score examination (MMSE) test. All 93 patients have been divided into three groups according to the results of MMSE. Patients in the first group had severe cognitive impairment and MMSE score below 17 (26.88%), patients in the second group with MMSE score 18–23 had moderate cognitive impairment (40.86%) and third group of patients have MMSE >24 and no cognitive impairment (32.26%). There were no significant differences between groups for gender, smoking habits and level of parathyroid hormone. Level of schooling was significantly different between groups of patients ( P < 0.001). Laboratory markers observed in this study with significant differences between groups were: IGF 1, IGFBP 3, erythrocytes and hemoglobin ( P < 0.001, P = 0.004, P < 0.001, P = 0.002, respectively). IGF 1 proved to be of great importance for evaluating cognitive status in our study. This marker was statistically different between groups ( P < 0.001) and Tukey post hoc analysis showed significant differences between all three groups (first and second group P = 0.045, second and third group P = 0.015, first and third group P < 0.001). Our data suggest that IGF 1 can be considered as novel biomarker for assessment of cognitive functioning in CKD patients, which can be of huge clinical importance.